Whole-genome sequencing of Listeria innocua recovered from retail milk and dairy products in Egypt - Ramadan, Hazem; Al-Ashmawy, Maha; Soliman, Ahmed M.; Elbediwi, Mohammed; Sabeq, Islam; Yousef, Mona; Algammal, Abdelazeem M.; Hiott, Lari M.; Berrang, Mark E.; Frye, Jonathan G.; Jackson, Charlene R. (Frontiers in Microbiology, 2023)
The similarity of the Listeria innocua genome with Listeria monocytogenes and their presence in the same niche may facilitate gene transfer between them. A better understanding of the mechanisms responsible for bacterial virulence requires an in-depth knowledge of the genetic characteristics of these bacteria. In this context, draft whole genome sequences were completed on five L. innocua isolated from milk and dairy products in Egypt. The sequencing results revealed the presence of only one antimicrobial resistance gene, fosX, in the L. innocua isolates. However, the five isolates carried thirteen virulence genes involved in adhesion, invasion, surface protein anchoring, peptidoglycan degradation, intracellular survival, and heat stress; all five lacked the Listeria Pathogenicity Island 1 (LIPI-1) genes. Multilocus sequence typing (MLST) assigned these five isolates into the same sequence type, ST-1085; however, single nucleotide polymorphism (SNP)-based phylogenetic analysis revealed 422 to 1091 SNP differences between our isolates and global lineages of L. innocua. The five isolates possessed ATP-dependent protease (clpL) gene, which mediates heat resistance, on a rep25 type plasmids. Blast analysis of clpL-carrying plasmid contigs showed approximately 99% sequence similarity to the corresponding parts of plasmids of L. monocytogenes strains 2015TE24968 and N1-011A previously isolated from Italy and the United States, respectively. Although this plasmid has been linked to L. monocytogenes that was responsible for a serious outbreak, this is the first report of L. innocua containing a clpL-carrying plasmids. Various genetic mechanisms of virulence transfer among Listeria species and other genera, could raise the possibility of the evolution of virulent strains of L. innocua. Such strains could challenge processing and preservation protocols and pose health risks from dairy products. Ongoing genomic research is necessary to identify these alarming genetic changes and develop preventive and control measures.